Complementary Feeding or Infants Aged 0-6 Months and The Related Factors: Complementary Foods for Breastfeeding - Lia Artikasari; Taty Nurti; Nelly Priyanti; Enny Susilawati; Herinawati Herinawati (Jurnal Kesehatan Komunitas, 2021)
Complementary food for breast milk is food or drink containing nutrition given to infants or children aged 6-24 months to meet their nutritional needs. Giving complementary foods to breast milk too early in infants can cause indigestion, diarrhea, food allergies, disturbances in appetite regulation and changes in appetite. This research was conducted in June 2019 in the Sungai Manau Health Center Work Area, Merangin Regency. This study is a descriptive study with a cross sectional design, with a sample of 96 mothers who have babies aged 0-6 months. The data analysis used was the chi square test with a significant level of = 0.05. Based on the research that has been done, it was found that there is a relationship between family support and the provision of complementary foods (p<0.01), there is a relationship between mother's knowledge and the provision of complementary foods (p<0.00), there is a relationship between family habits and the provision of complementary foods (p<0.00). <0.00). Based on the results of the study, it is hoped that it can provide input in the Sungai Manau Health Center Work Area in order to increase socialization to the community regarding the provision of complementary feeding.